LoRaWAN-Based Communication for Autonomous Vehicles: Performance and Development - Saharuna, Saharuna; Adiprabowo, Tjahjo; Yassir, Muhammad; Nurdiana, Dian; Adi, Puput Dani Prasetyo; Kitagawa, Akio; Satyawan, Arief Suryadi (Prodi Teknik Informatika FIK Universitas Muslim Indonesia, 2024)
Automotive technology in the future continues to develop with a variety of sophistication, especially in vehicles that can move on their own, this research is new from previous developments, intelligent vehicles can be seen from various system developments ranging from the ability to find parking positions, have the right navigation system, and are equipped with various artificial senses such as LiDAR, Smart Camera, Artificial Intelligence, and various components for telecommunications. A small part that will be discussed in this research is in terms of data communication. The development of intelligent vehicles in a broader scope can be included in one of the categories to build a Smart City. In the analysis system, this research develops in terms of analyzing the possibility of data collisions or how to avoid them, with various methods that can be developed and approached comprehensively using LoRaWAN, so that a method can be determined using LoRaWAN Communication and LoRa Modules that can have an important impact in the development of intelligent vehicles or autonomous vehicles for Smart City. In this paper, the LoRa data transmission approach is to use the GPS Module, the GPS Module data is sent from each car to the nearest LoRaWAN Gateway, the car can automatically select the nearest Gateway for data optimization, reducing Packet Loss and Signal Attenuation due to LoRa data communication in the NLOS area, This article still uses data transmission simulation using MATLAB and is planned to be applied to Smart vehicles directly, the contribution of this research is the discovery of a new method in terms of LoRaWAN-based multi-point data transmission that can avoid data collisions from the position of intelligent vehicles in Mobile or moving, in building Smart City technology in the future.